STOOL FORM SCALE AS AN INDICATOR OF KLUTUK BANANA (MUSA BALBISIANA COLLA) FRUIT EXTRACTS INHIBITION EFFECT AGAINST SHIGELLA DYSENTERIAE ATCC 13313 IN VIVO - Kusuma, Sri Agung Fitri; Wardhani, Puspagita; Febrina, Ellin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Stools consistency is a common symptom indicating in dysenteriae. The aim of this study was to investigate the inhibitory effect of the klutuk banana fruit extract that determine different degrees of stool consistency in dysentery induced by Shigella dysenteriae ATCC 13313. Methods: The extraction of klutuk banana fruits was prepared using a maceration method. The antidysenteriae activity of the klutuk banana extract was evaluated in vivo. The specific pathogen-free mice were intraperitoneally injected with S. dysentriae suspension cell. Observations were made for 7 days on body weight of mice, total fecal weight every 24 hrs and consistency of stool. The level of stool consistency was measured based on Bristol Stool Chart. Results: The results indicated that the body weight of each group was decreased the day after induction and the stool consistency was at level 5-6. However, both test groups could achieve the ideal type of stool (type 4) in the same period of time as a group with ciprofloxacin treatment. Conclusion: It can be concluded that the ethanol extract of klutuk banana fruits is highly potent as natural antidysenteriae against S. dysenteriae.